Simultaneous photocatalytic Cr(VI) reduction and phenol degradation over copper sulphide-reduced graphene oxide nanocomposite under visible light irradiation: Performance and reaction mechanism. (April 2021) - Cherifi, Yacine; Barras, Alexandre; Addad, Ahmed; Ouddane, Baghdad; Roussel, Pascal; Chaouchi, Ahcène; Szunerits, Sabine; Boukherroub, Rabah
Abstract: The contamination of water by synthetic organic molecules and trace metals is a growing challenge, in spite of the enormous research efforts being made in the field of water treatment. In this study, reduced graphene oxide-copper sulphide (rGO-CuS) nanocomposites of different rGO/CuS (2/1, 1/1, 1/2) molar ratios were fabricated via a facile one-step hydrothermal method. The nanocomposite materials, named hereafter as 2rGO-CuS, rGO-CuS and rGO-2CuS, were characterized using various analytical techniques, including X-ray diffraction (XRD), Raman spectroscopy, transmission electron microscopy (TEM), energy dispersive X-ray (EDX) spectroscopy, X-ray photoelectron spectroscopy (XPS) and UV–visible spectrophotometry. The photocatalytic performance of the nanocomposites was assessed under visible light irradiation (λ > 420 nm) for the simultaneous photocatalytic reduction of Cr(VI) and phenol degradation. It was found that rGO-2CuS achieved a remarkable enhancement of the photocatalytic activity among the prepared nanocomposites for the degradation of phenol and reduction of Cr(VI). Therefore, the simultaneous photocatalytic phenol degradation and Cr(VI) reduction over rGO-2CuS sample was further investigated. The experimental results revealed that rGO-2CuS catalyst maintained good degradation efficacy of mixed pollutants after 6 runs and dissolved oxygen was found to be essential to promote Cr(VI) reduction and phenol degradation. A detailed photocatalytic activity under visible light irradiation mechanism was proposed based on quenching experiments and fluorescence measurements. Highlights: rGO-CuS photocatalyst was prepared by a one-step hydrothermal approach. It achieved high efficiency for the simultaneous Cr(VI) reduction and phenol degradation. It exhibited improved stability over 5 cycles. Plausible mechanism and degradation pathway were proposed.